2013
DOI: 10.1177/000348941312201201
|View full text |Cite
|
Sign up to set email alerts
|

Open Staple Diverticulectomy for a Large Recurrent Zenker's Diverticulum: Still a Valid Procedure

Abstract: Although endoscopic laser cricopharyngeal myotomy and stapler diverticulostomy have become standard treatments for Zenker's diverticulum, this case of a large recurrent diverticulum illustrates a situation in which older techniques may be preferred. Use of the mechanical stapler allowed for a shorter surgery time than traditional suture techniques, and the potential for an earlier return to a normal diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In humans, various staplers, including TA staplers, are widely used for esophageal procedures including removal of esophageal diverticula 17,18 . Their use has also been described in dogs 10,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, various staplers, including TA staplers, are widely used for esophageal procedures including removal of esophageal diverticula 17,18 . Their use has also been described in dogs 10,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews demonstrated a mortality of 0.2% to 0.4% with endoscopic approaches, compared with 0.6% to 0.9% with open procedures 12,13 . Notably, endoscopic procedures are not feasible for patients with unfavorable anatomy, recurrent diverticulum, or small or large diverticulum 14–17 . Furthermore, open procedures have a lower rate of symptom recurrence and need for revision procedures 18 .…”
mentioning
confidence: 99%
“…12,13 Notably, endoscopic procedures are not feasible for patients with unfavorable anatomy, recurrent diverticulum, or small or large diverticulum. [14][15][16][17] Furthermore, open procedures have a lower rate of symptom recurrence and need for revision procedures. 18 When an endoscopic approach is feasible, options include stapler, 19 carbon dioxide laser, 20 and potassium titanyl phosphate (KTP) laser.…”
mentioning
confidence: 99%